Early diagnosis of giant cell arteritis - the basis of good outcome: Zgodnja diagnoza velikoceličnega arteritisa - osnova za dober izhod - Holc, Iztok (Acta Medico-Biotechnica, 2021)
Purpose: If untreated, giant cell arteritis can lead to blindness and stroke. The study objectives were to assess diagnostic procedures and treatment in early interventional clinic in University Clinical Centre Maribor in patients with temporal arteritis. Methods: Retrospective study (from 2012 to 2017) of patients diagnosed with temporal arteritis. We assessed epidemiological data, delay of diagnosis, and diagnostic procedures. Results were assessed with statistical methods (SPSS 22.0). Main goal: The main goal was to determinate the delay in days between symptom onset and admission to the interventional rheumatology clinic and to assess the causes of delay. Results: Fifty-three GCA (66 % female) patients with mean age 76.25 (from 63–89 years) years were included. Mean time duration of symptoms before admission to our early interventional clinic was 33.74 (0–180) days. The diagnostic procedure was completed in mean time of 2.04 days from the presentation at our interventional rheumatology clinic. The median time to the temporal artery biopsy (TAB) performed in 52 /53 patients was 2 days, with the median 2 days to the preliminary histological results from admission. TAB was positive in 43 (81.1%) of cases. The median time from admittance to colour Doppler sonography (CDS) of aortic arch branches was 2 days and it was positive in all 19 (35.8%) performed cases. 16 (30.2%) patients had polymyalgia rheumatica, 35 (66%) patients had visual disturbances, permanent one eye blindness occurred in 12 (22.64%) patients, and 2 (2.8%) patients experienced permanent blindness on both eyes. Seventeen patients (32.1%) were initially treated with intravenous methylprednisolone pulse. The mean initial dose of oral methylprednisolone was 45.55 (± 15.54) mg. All patients received low dose Aspirin. Conclusion: Early diagnosis and treatment of giant cell arteritis are very important as miss- or non-diagnosed GCA can lead to permanent blindness of the patient. With better education and public awareness, better access and better professional education of primary care physicians, and early admission to secondary interventional clinics we might spare these patients from the devastating consequences of the GCA.